Fishing cats [book with audioplayer] - Kenney, Karen Latchana (Blastoff! readers. Animals of the wetlands., 2021)
A fishing cat dives into the water. In seconds, it comes back to the surface with its latest meal! In this leveled text, young readers will explore the fascinating lives of fishing cats, from where they live to what they eat. Along the way, they'll learn about the body parts and behaviors that have helped the cats adapt to their wetland habitat. Special features call out the range, physical adaptations, and diet of these wetland predators.